Analisis Variabel Perubahan Suhu Terhadap Karakteristik Tegangan Tembus Dielektrik Udara - Christiono; Miftahul Fikri; Iwa Garniwa MK; Kartika Tresya Mauriraya (Jurnal Teknik: Media Pengembangan Ilmu dan Aplikasi Teknik, 2023)
The problem in the tropics is the effect of temperature changes on the high voltage system, resulting in isolation around the electricity distribution in the 20 kV cubicle, which can trigger the insulation failure (breakdown voltages) on a feeder. To reduce the occurrence of power outages due to insulation failure with changing temperatures, direct testing is carried out by providing temperature variations ranging from 30oC to 90oC. To correctly understand the phenomenon, testing should be carried out. The test is carried out every 5 oC temperature increase. Based on the research results, a graph is obtained that explains the decrease in the breakdown value at 50oC, which causes the insulation breakdown voltage to be 27kV, and the decrease in the breakdown voltage at 90oC, which causes the insulation breakdown voltage to decrease to 22kV. Based on experiments, it can be concluded that the greater the temperature rise, The breakdown voltage appears more quickly. Thereafter, the data from the research results were tested using the linear regression analysis method, so that a MAPE obtained 3.89% and an RMSE obtained 1.33 were obtained with an average percentage obtained 0.37%.